The struggle for recognition and self-harm practices in the identity constitution in the student experience - Kaplan, Carina Viviana (2021)
The present work aims to interpret the relationships between the feeling of recognition that students build and the production of violence against their own body. The arguments presented refer to the results of a socio-educational research in which the meanings that students construct about emotions and bodies and their relationship with the production of violence in two secondary schools in the Province of Buenos Aires, Argentina. Based on the testimonies produced by the socio-educational study where 40 students from two state public schools in peripheral urban areas of the city of La Plata, Province of Buenos Aires, Argentina were interviewed, it is possible to affirm that the need for self-assertion constitutes an axis central in the processes of juvenile subjectivation.  In line with the qualitative approach adopted, in-depth interviews and focus groups were selected as data collection instruments, since they constitute relevant tools when seeking to understand the subjective experience of the participants. From the accounts of experiences of cuts to the skin, it is possible to argue that self-destruction practices are closely linked to struggles for recognition. Faced with the gaze and the perceived judgments, young people develop different strategies to face social pain in order to restore social self-worth.